Improving Shared Space to Reduce Traffic Risk: Analytic Study of Mawlawi Street in Sulaimani, Iraq: Improving shared space to reduce traffic risk - Agha, Shava Shirwan; Kader Maruf, Sherko Karim (Kurdistan Journal of Applied Research, 2022)
Within the field of traffic street design, the shared space approach points to create streets from simple traffic frameworks to public spaces, compelling higher interaction between street clients. In this paper we create the essentials for a micro-simulation tool based on the Social force model, to illustrates the movement of street clients in such formats. Working with the observed behavior of clients in a pedestrian-friendly crossing point within the city of Sulaimani a multi-layer organized models is created, in which each layer is assigned to handle different circumstances, from free-flow developments to client intuitive in crowded circumstances. Visibility pie charts and figures estimations are used for planning directions of street clients for the free flow movement